MIGHTEE-HI: discovery of an H I-rich galaxy group at z = 0.044 with MeerKAT - Ranchod, S; Deane, RP; Ponomareva, AA; Blecher, T; Frank, BS; Jarvis, MJ; Maddox, N; Mulaudzi, W; Glowacki, M; Hess, KM; Tudorache, M; Verdes-Montenegro, L; et al. (Oxford University Press, 2021)
We present the serendipitous discovery of a galaxy group in the XMM-LSS field with MIGHTEE Early Science observations. 20 galaxies are detected in H I in this z ∼ 0.044 group, with a 3σ column density sensitivity of NHI=1.6×1020cm−2⁠. This group has not been previously identified, despite residing in a well-studied extragalactic legacy field. We present spatially resolved H I total intensity and velocity maps for each of the objects which reveal environmental influence through disturbed morphologies. The group has a dynamical mass of log10(Mdyn/M⊙)=12.32⁠, and is unusually gas-rich, with an H I-to-stellar mass ratio of log10(f∗HI)=−0.2⁠, which is 0.7 dex greater than expected. The group’s high H I content, spatial, velocity, and identified galaxy type distributions strongly suggest that it is in the early stages of its assembly. The discovery of this galaxy group is an example of the importance of mapping spatially resolved H I in a wide range of environments, including galaxy groups. This scientific goal has been dramatically enhanced by the high sensitivity, large field-of-view, and wide instantaneous bandwidth of the MeerKAT telescope.